A Guide to Countries of the World - Stalker, Peter (Oxford Oxford University Press, 2013)
This A-Z guide provides a wealth of information for every country in the world. Each entry offers a brief history and outlines contemporary social, economic, political and religious issues. For every country there is a map and a quick-reference fact box containing data and statistics including languages, population, GDP, capital city, life expectancy, and more. An appendix of indicator tables includes statistics on income and poverty, health and population and a second appendix features regional groupings, such as the EU and the African Union, with useful web links. Revised and fully updated, the Third Edition is ideal for students and teachers of geography, politics, economics, and world history, and it is a perfect home reference book. From major powers such as the United States or China, to hot spots such as North Korea or Iran, to little known nations such as Mayotte, Kiribati, or Nauru, this essential guide is the first place to turn for information on the world around us.
Include Tables.
Keywords: Gazetteers -- World politics -- Geography